2015
DOI: 10.1038/srep10725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of straw mulch on soil water and winter wheat production in dryland farming

Abstract: The soil water supply is the main factor that limits dryland crop production in China. In a three-year field experiment at a dryland farming experimental station, we evaluated the effects of various straw mulch practices on soil water storage, grain yield, and water use efficiency (WUE) of winter wheat (Triticum aestivum). Field experiments were conducted with six different mulch combinations (two different mulch durations and three different mulch amounts): high (SM1; 9000 kg ha−1), medium (SM2; 6000 kg ha−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…FPS had a higher SWS than CK, although there were no significant differences ( P > 0.05) between treatments in either of the two growing seasons. This result is consistent with previous studies 23 , 30 , 31 , indicating that the reduction in evaporation and increased water retention under straw mulch was limited and relatively short-lived because of the rapid degradation of the mulch with high microbial activity stimulated by good nutrient supply. From 41–60 cm, the SWS under RFPS was highest among all treatments over both growing seasons ( P < 0.05).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…FPS had a higher SWS than CK, although there were no significant differences ( P > 0.05) between treatments in either of the two growing seasons. This result is consistent with previous studies 23 , 30 , 31 , indicating that the reduction in evaporation and increased water retention under straw mulch was limited and relatively short-lived because of the rapid degradation of the mulch with high microbial activity stimulated by good nutrient supply. From 41–60 cm, the SWS under RFPS was highest among all treatments over both growing seasons ( P < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…However, this has resulted in a progressive depletions of SWS 22 . Some studies have reported that the drylands require higher and more stable water availabilities to produce higher winter wheat yields 16 , 23 , 24 . Therefore, the research aimed at increasing SWS and WUE has the potential to be highly beneficial for dryland farming systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was possibly due to the effect of farming methods, wheat-maize rotations are dominant cropping systems in Yingshang whereas the farming methods of Longkang is wheat after rice. Previous studies also showed that there are differences among different farming methods in root system biomass and root system volume [20,21]. 6% pyraclostrobin • difenoconazole FSC and 6% difenoconazole •thiram FSC were best for promoting the germination and growth of wheat in Longkang and Yingshang, respectively, which provided better wheat biomass than did the positive control, e.g., Celest Top, FSC (difenoconazole + fludioxonil + thiamethoxam, 2.2 + 2.2 + 22.6%, respectively).…”
Section: The Comparison Results Of Field Trialmentioning
confidence: 97%
“…In the arid and semiarid regions of China, crop residues incorporated into soil can lower soil bulk density, increase soil porosity, and increase the quantities of soil organic C and soil-available N, P, and potash in the plow layer (0-15 cm), thereby increasing the wheat yield (Wang et al, 2013;Wei et al, 2015;Yu et al, 2015). In the North China Plain, spreading crop residues over soil as mulch promotes the growth of wheat plants and increases grain yield by reducing soil runoff, improving soil infiltration capacity, increasing its moisture content, and optimizing the nutrient cycle in the soil-crop system (Su et al, 2007;Zhang et al, 2015;Mu et al, 2016). Moreover, the greater the amount of crop residues used as mulch, the greater the reduction in the evaporation of soil moisture and the greater the increase in yield within a certain range .…”
Section: Yield Responses Of Wheat To Crop Residue Returning In China:mentioning
confidence: 99%